1991
DOI: 10.1152/jappl.1991.70.3.1075
|View full text |Cite
|
Sign up to set email alerts
|

Washed human platelets prevent ischemia-reperfusion edema in isolated rabbit lungs

Abstract: Washed human platelets prevent edema formation in isolated rabbit lungs infused with xanthine oxidase, an enzyme that injures endothelial membranes by generating extracellular oxidants. We hypothesized that platelets would similarly preserve membrane permeability in isolated lungs exposed to ischemia-reperfusion injury, a model that perturbs endothelial cells by the generation of intracellular oxidants. Isolated perfused rabbit lungs (IPL) were exposed to warm ischemia-reperfusion to cause lung edema. The infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Hence, mechanisms unrelated to platelet-derived oxidants must cause nitrotyrosine formation during the hourlong exposures. In this situation, platelets appear to antagonize the oxidative process; a phenomenon reported in several models of oxidative stress (24,25). The concentration of nitrotyrosine was the same whether rats were exposed to 1000 ppm CO for 1 h or to the full, standard CO model which involved exposure to 1000 ppm for 40 min and then to 3000 ppm for 20 min (Fig.…”
Section: Effect Of Platelets On Nitrotyrosine Formation Based On Thementioning
confidence: 75%
“…Hence, mechanisms unrelated to platelet-derived oxidants must cause nitrotyrosine formation during the hourlong exposures. In this situation, platelets appear to antagonize the oxidative process; a phenomenon reported in several models of oxidative stress (24,25). The concentration of nitrotyrosine was the same whether rats were exposed to 1000 ppm CO for 1 h or to the full, standard CO model which involved exposure to 1000 ppm for 40 min and then to 3000 ppm for 20 min (Fig.…”
Section: Effect Of Platelets On Nitrotyrosine Formation Based On Thementioning
confidence: 75%
“…25 Platelets preserve the normal endothelial permeability in the lungs exposed to ischemia-reperfusion injury by releasing platelet glutathione redox cycle antioxidants. 26 Lo et al noted an increase in pulmonary vascular permeability in animals with thrombocytopenia. 27 Platelets limit the transfer of water, proteins, and red blood cells out of the vessels by contributing to the basal barrier integrity of the alveolar capillaries.…”
Section: Discussionmentioning
confidence: 98%
“…Platelets have antioxidant effects, and antioxidant‐intact platelets decrease oxidant‐induced lung edema by preventing increased membrane permeability . Platelets preserve the normal endothelial permeability in the lungs exposed to ischemia–reperfusion injury by releasing platelet glutathione redox cycle antioxidants . Lo et al .…”
Section: Discussionmentioning
confidence: 99%
“…In a study of isolated sheep lungs, perfusion with platelet-free solutions worsened lung fluid accumulation, indicating that platelets protect against pulmonary edema by an unknown mechanism (68). In isolated perfused rabbit lungs, human platelets reduced lung edema induced by oxidant challenge or by ischemia-reperfusion (69, 70). In vitro studies also demonstrated that intact platelets reduce labeled-albumin transfer across cultured pulmonary artery endothelial monolayers (65).…”
Section: Platelets In Pulmonary Vascular Integrity and Barrier Functionmentioning
confidence: 99%